Effect of gibberellic acid on postharvest shelf-life and quality of tomato - Sharma, Anusha; Khanal, Amit; Dhital, Bibek (Journal of Postharvest Technology, 2018)
Tomato is one of the universally grown and widely consumed vegetable with high nutritive and commercial value. High perishable nature of tomato leads to huge post-harvest losses and thus practices to extend its shelf-life is must. Therefore, this research was carried out to study the effect of Gibberellic Acid (GA3) on the post-harvest shelf-life and quality of tomato. The research was conducted in the horticulture laboratory of IAAS, Lamjung Campus with four treatments viz. 0.05% (T1), 0.1% (T2), 0.3% (T3) GA3 and control (T4) in Completely Randomized Design with six replications. Tomato fruits (var. Dalila) were harvested at the breaker stage in January, 2018. Fruits were kept on trays at room temperature of around 20◦C after dipping on different GA3 concentrations for 15minutes with. Quality and quantity parameters that serve as indicators of ripening stages viz. physiological weight loss, color, decay percentage, total soluble solids and titrable acidity and shelf life were studied. Results showed that GA3 has significant effect on study parameters. Among different GA3 concentrations, treatment with 0.1% GA3 was found to be best with significantly lower weight loss (2.429%), significantly lower total soluble solid (5.3166) and significantly higher titrable acidity (0.849%). Longer shelf-life (96.33days) was observed in 0.1% compared to 0.3% (85.667 days) and 0.05% (83 days).Significantly higher weight loss (5.578%) and lower titrable acidity (0.647%) was observed in control. T2 was found best for post-harvest treatment of tomato. However, its impact on other nutritional aspect and health must be further investigated before application.